2006
DOI: 10.1002/adma.200502487
|View full text |Cite
|
Sign up to set email alerts
|

Facile Generation of Fullerene Nanoparticles by Hand‐Grinding

Abstract: When particles become smaller than 100 nm, they exhibit properties that are not observed for molecules or their bulk counterparts.[1] Such particles are building blocks for nanotechnology-derived applications such as single-electron devices, ultradense recording media, bioelectronic devices and sensors, bioimaging, optoelectronic devices, catalysis, and chemical sensors, as well as energy conversion and storage. [1,2] The obvious approach to prepare small particles is a top-down approach, in which bulk solid i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
99
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 20 publications
0
99
1
Order By: Relevance
“…The second method to obtain nanosized particles is by sonication. Sonication uses sound energy with frequencies of more than 20 kHz to agitate particles inside a sample Deguchi et al (2006). It can help to produce even dispersion of nanoparticles in liquid and it is very useful especially when it is not possible to stir the sample.…”
Section: Fig 1 Summary Of Tm Doped Al Nanoparticles Synthesis Routementioning
confidence: 99%
“…The second method to obtain nanosized particles is by sonication. Sonication uses sound energy with frequencies of more than 20 kHz to agitate particles inside a sample Deguchi et al (2006). It can help to produce even dispersion of nanoparticles in liquid and it is very useful especially when it is not possible to stir the sample.…”
Section: Fig 1 Summary Of Tm Doped Al Nanoparticles Synthesis Routementioning
confidence: 99%
“…Reactive oxygen species are considered as a significant factor contributing to the toxicity of nC 60 [22][23][24]. On the contrary, some studies showed that nC 60 did not have potential toxicity [9,[25][26][27], and could even act as free radical scavenger [7]. Therefore, due to different prepared methods and organisms used, there is still no consensus until now in the literature regarding the toxicity of nC 60 .…”
mentioning
confidence: 93%
“…However, water stable nano-aggregates of C 60 (termed nC 60 ) can be formed from pristine C 60 in certain conditions, for example, by solvent exchanging (such as tetrahydrofuran and toluene) [8], hand-grinding [9], and prelonged stirring in water [10]. As it may be a most environmentally relevant form of C 60 [11], nC 60 has recently caused much concern about its toxicity to humans and the environment, though its concentration is usually less than 10 mg/L in aquatic environment [12,13].…”
mentioning
confidence: 99%
“…Several procedures were reported (Table 2), mostly involving the solubilisation in water by solvent exchange using different organic solvents (ethanol, toluene, THF and acetone) via sonication or mechanical stirring [6,8,[10][11][12][13][14][15]82] . Additionally, the direct solubilisation of C 60 in water was also reported via sonication [12] or extended stirring [13][14][15] . The preparation conditions vary from one study to another in terms of stirring rate, sonication power, time used for sonication and/or stirring, amount of organic solvent and the filtration step.…”
Section: Effect Of the Preparation Methods On The Morphology And Size mentioning
confidence: 99%
“…Despite the fact that fullerenes are very hydrophobic with very low solubility in water, around 8 ng L -1 for C 60 [5] , several methods have been developed to disperse these compounds in aqueous media [6][7][8][9][10][11][12][13] leading to the formation of stable colloidal aggregates (nC 60 ), a highly hydrophilic supramolecular complex consisting of С 60 enclosed into a hydrated shell containing 24 water molecules: C 60 @(H 2 O) 24 . The aqueous suspensions of nC 60 are amber coloured and are stable for months to years at very low ionic strength [14,15] .…”
Section: Introductionmentioning
confidence: 99%